Alloy design and adaptation for additive manufacture - Clare, A. T.; Mishra, R. S.; Merklein, Marion; Tan, H.; Todd, I.; Chechik, L.; Li, J.; Bambach, M. (Journal of Materials Processing Technology, 2022)
In this review the authors provide a comprehensive insight into additive manufacturing process mechanics which explore how thermodynamics give rise to characteristic microstructure and property. Discussion is then given over to how solidification microstructure is modified using processing conditions and utilisation of traditional casting methods which give rise to grain refinement and some cases ‘texture by design’. The review then makes observation and provides analysis on the typical material types reported in powder bed fusion and directed energy deposition. These are organised to efficiently highlight the key observations in terms of alloy creation and adaption with a specific focus on the relevant additive manufacturing technique. The emergent alloy families are also explored alongside the rapidly expanding topic of functionally graded alloys produced by the breadth of additive manufacturing techniques. The review concludes with a detailed critique of the state-of-the-art and an examination of where opportunities exist to advance the interdependency between process and emergent alloys exhibiting superior properties. The authors propose several areas worthy of consideration and attempt to provide inspiration for our community in the pursuit of new alloys and accompanying process designs for additive manufacturing.
CRIS-Team Scopus Importer:2021-10-08
Keywords: Additive manufacture; Alloy development; Directed energy deposition; Powder bed fabrication